Penggunaan Media Teknologi Artificial Intelligence Dalam Meningkatkan Kemampuan Berbahasa Arab Di PPM Rahmatul Asri - Ilham MR; Saepudin Saepudin; Herdah Herdah; Darmawati Darmawati; Kaharuddin Ramli (Journal on Education, 2024)
This thesis discusses the use of Artificial Intelligence technology media in improving Arabic language skills at Rahmatul Asri Islamic Modern Boarding School. This research aims to explore the differences in improving Arabic language skills between the use of Artificial Intelligence technology media and the use of Power Point media or conventional learning media as a comparison. The research used a Quasi Experimental method with a two group pretest-posttest design, involving 56 samples of students from classes X and XI MA PPM Rahmatul Asri. Data was collected through Arabic language proficiency tests before and after treatment. The results showed a significant increase in the students' Arabic language skills. The average learning outcome score based on the students' pre-test (72.00) increased to (88.86) based on the average post-test score after treatment. Data analysis using the t-test shows that this increase is significant, with a sig (2-tailed) value of 0.000 < 0.05, which indicates that this difference did not occur by chance. The conclusion of this research is that the use of Artificial Intelligence technology media is effective in improving students' Arabic language skills. Interactive and interesting learning media has been proven to be able to create a more active and enjoyable learning atmosphere. It is recommended that this method be applied more widely in other Islamic boarding schools, and that teachers be given training to optimize the use of Artificial Intelligence media in learning.